Expressive Functions From Movie The Boy and The Heron - Ni Made Putri Lestari; I Dewa Ayu Devi Maharani Santika (Universitas Islam Negeri Palopo, 2025)
This study explores the expressive function of language in Hayao Miyazaki’s 2023 animated film The Boy and the Heron through a sociolinguistic lens. Drawing on Leech’s (1981) classification of language functions and Halliday’s (1994) contextual framework, the research analyses how characters express emotions such as happiness, anger, sadness, and regret. A qualitative method was used to examine five selected dialogues from the film, which generated 35 data points encompassing various emotional and social dynamics. The relationship between the selected dialogues and the total data points lies in the fact that each dialogue contained multiple expressive utterances, resulting in a richer set of data for analysis. The findings reveal that happy expressions were the most frequent (28.57%), followed by sadness and regret (25.71% each), and anger (20%). Expressive utterances were found to be linguistically nuanced and closely linked to the characters’ psychological states and relational contexts. The study underscores the importance of expressive language in shaping character development and emotional depth, enhancing audience empathy and engagement. Overall, it contributes to a broader understanding of how expressive functions operate in cinematic discourse, particularly within the cultural and narrative framework of Miyazaki’s storytelling.